How Compounding Pharmacies Fill Critical Gaps in Pediatric Drug Development Processes: Suggested Regulatory Changes to Meet Future Challenges - Robert B. MacArthur; Lisa D. Ashworth; Keming Zhan; Richard H. Parrish (MDPI AG, 2022)
Drugs administered to children in the United States fall into two broad categories: (1) those that have followed the US Food and Drug Administration (US-FDA) pediatric drug approval process and are marketed as finished dosage forms with pediatric labeling; and (2) all others, many of which are used "off-label". The use of most drug products in pediatrics is still off label, often requiring special preparation, packaging, and, in some cases, compounding into preparations. The latter category includes compounded preparations that incorporate either a US-FDA approved finished dosage form (e.g., a sterile solution, sterile powder, nonsterile capsules, oral solution, crushed tablets, etc.), or rely on bulk active pharmaceutical ingredients (APIs). Compounded preparations are prepared for individual patients in 503A pharmacies, or on a larger scale and not just for specific patients, in licensed 503B establishments. Critical gaps in the current drug approval process for finished dosage forms have created a proverbial "Gordian knot" that needs to be untangled thoughtfully to facilitate increased production and approval of vitally needed medications for pediatric patients. This opinion will describe current regulatory processes pertaining to pediatrics-only drug approval in the United States. Additionally, discussed are steps required for a product to acquire pediatric labeling. Gaps in regulatory approval pathways for both manufactured and compounded pediatric drugs will be identified, especially those that complicate and slow development and availability to patients. Finally, suggestions for regulatory modifications that may enhance pediatric product development strategies for both manufacturers and compounders are suggested.